2004
DOI: 10.1111/j.1360-0443.2004.00755.x
|View full text |Cite
|
Sign up to set email alerts
|

Abstinence rates and predictors of outcome for smoking cessation: do Brazilian smokers need special strategies?

Abstract: The higher percentage of smoking cessation was achieved using multiple therapies (counseling + NRT + bupropion). The only significant predictor of failure detected was severe nicotine dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
1
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 37 publications
5
20
1
5
Order By: Relevance
“…(23,24) This preponderance of females can be explained by a possible selection bias, since it has been shown that women seek medical treatment for smoking cessation more frequently than do men. (21,(25)(26)(27) The mean age was higher in the COPD group than in the non-COPD group, which is consistent with the natural history of the disease. (28) In addition, only 3% of the patients with COPD had had more than 8 years of schooling, a finding that is also in accordance with those reported in the literature, which indicate that the frequency of COPD is inversely proportional to the level of education of the smoker.…”
Section: Discussionmentioning
confidence: 54%
“…(23,24) This preponderance of females can be explained by a possible selection bias, since it has been shown that women seek medical treatment for smoking cessation more frequently than do men. (21,(25)(26)(27) The mean age was higher in the COPD group than in the non-COPD group, which is consistent with the natural history of the disease. (28) In addition, only 3% of the patients with COPD had had more than 8 years of schooling, a finding that is also in accordance with those reported in the literature, which indicate that the frequency of COPD is inversely proportional to the level of education of the smoker.…”
Section: Discussionmentioning
confidence: 54%
“…Though included in the initial regression model due to its theoretical importance, neither HSI nor its interaction with group was a signifi cant predictor in the context of the other independent variables. This is contrary to results from studies in which high levels of dependence predicted failure to quit ( Chandola, Head, & Bartley, 2004 ;Chatkin, 2004 ;Ferguson et al, 2003 ;Grandes, Cortada, Arrazola, & Laka, 2003 ;Hymowitz et al, 1997 ;Ji et al, 2005 ).…”
Section: Null Predictors Of Duration Of Quittingcontrasting
confidence: 55%
“…2 Despite efforts in implementing the Brazilian National Program for Tobacco Control, the rate of successful treatment is still low (about 20%). 3 The odds of success can be improved by further knowledge of the characteristics of individuals who adhere to the program, so that treatment can be adjusted to the specific characteristics of the target population. 4 The aim of this study was to describe the characteristics of smokers who seek help to quit smoking in Brazilian public health units, based on the experience of a primary health care unit that covers a poor community in the city of Rio de Janeiro.…”
Section: Introductionmentioning
confidence: 99%